Population of P-solubilizer bacteria, available P, P Uptake and chili yield affected by bioameliorants and nutrient - Fitriatin, Betty Natalie; Dita, Limbong Agatha Dita; Fauziah, Nicky Oktav Fauziah; Simarmata, Tualar Simarmata; Fakhrurroja, Hanif Fakhrurroja (Jurnal AGRO, 2025)
The consumption of red chili (Capsicum annum L.) increased annually, requiring higher productivity. However, this is not supported by optimal soil fertility which has a low nutrient content. This research aimed to examine the interaction between bioameliorant dose (B) and nutrient solution application interval (F) on phosphate solubilizing bacteria (PSB), available P, P uptake, fruit weight per plant, and fruit weight per fruit. The research was conducted using a Factorial Randomized Block Design with two factors and three replications (bioamelioran dosage: 0, 3, 6 t ha-1) and nutrient solution application interval: every one, three, and five days. The results showed an interaction effect on fruit weight with the best treatment being a bioameliorant dose of 3 t ha-1 and a nutrient solution interval once a day. The bioameliorant increased available P and the nutrient solution interval had influenced on soil available P and fruit weight per plant. Application of a bioameliorant dose of 3 t ha-1 and nutrient solution interval once a day produced the highest yield of chili. ABSTRAK Konsumsi cabai merah (Capsicum annum L.) meningkat setiap tahunnya, sehingga membutuhkan produktivitas yang lebih tinggi. Namun, hal ini tidak didukung oleh kesuburan tanah yang optimal serta memiliki kandungan nutrisi yang rendah. Penelitian ini bertujuan untuk mengetahui interaksi antara dosis bioamelioran (B) dan interval pemberian larutan hara (F) terhadap bakteri pelarut fosfat (BPF), P-tersedia, serapan P, bobot buah per tanaman, dan bobot buah per buah. Penelitian dilakukan menggunakan Rancangan Acak Kelompok Faktorial dengan dua faktor dan tiga ulangan (dosis bioamelioran: 0, 3, 6 t ha-1) dan interval pemberian larutan hara: setiap satu, tiga, dan lima hari. Hasil penelitian menunjukkan adanya pengaruh interaksi terhadap rerata berat buah, dengan perlakuan terbaik adalah dosis bioamelioran 3 t ha-1 dan interval pemberian larutan hara satu kali sehari. Pemberian bioamelioran mampu meningkatkan P-tersedia. Interval pemberian larutan hara mempengaruhi kandungan P-tersedia tanah dan bobot buah per tanaman. Aplikasi bioamelioran dengan 3 t ha-1 dan interval pemberian larutan hara satu kali sehari menghasilkan hasil cabai merah tertinggi. Kata kunci: Cabai Merah, Mikroba Menguntungkan, Pembenah Tanah, Unsur Hara